1995
DOI: 10.1074/jbc.270.20.11882
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Function Analysis of Human Glucose-6-phosphatase, the Enzyme Deficient in Glycogen Storage Disease Type 1a

Abstract: Glucose-6-phosphatase (G6Pase) is the enzyme deficient in glycogen storage disease type 1a, an autosomal recessive disorder. We have previously identified six mutations in the G6Pase gene of glycogen storage disease type 1a patients and demonstrated that these mutations abolished or greatly reduced enzymatic activity of G6Pase, a hydrophobic protein of 357 amino acids. Of these, four mutations (R83C, R295C, G222R, and Q347X) are missense and one (Q347X) generates a truncated G6Pase of 346 residues. To further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
94
0
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(101 citation statements)
references
References 20 publications
5
94
0
2
Order By: Relevance
“…Mutations at the equivalent position of Arg83 (1.08) in human G6Pase (alignment is shown in Fig. S1A) to any other amino acid residue, including Lys, also abolished enzyme activity (21). In particular, mutation of R83C has been directly related to glycogen storage disease type 1a (10,22).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations at the equivalent position of Arg83 (1.08) in human G6Pase (alignment is shown in Fig. S1A) to any other amino acid residue, including Lys, also abolished enzyme activity (21). In particular, mutation of R83C has been directly related to glycogen storage disease type 1a (10,22).…”
Section: Resultsmentioning
confidence: 99%
“…His163 (2.04) stabilizes the transition state intermediate and catalyzes the cleavage of the terminal PO 4 group from the substrate (18). Mutations at the equivalent position of His119 (2.04) in human G6Pase to any other amino acid residue have been shown to abolish its enzyme activity (21). In ecPgpB, conserved Arg104 (1.08) interacts with the catalytic His207 (3.08) and potentially with the substrate.…”
Section: Resultsmentioning
confidence: 99%
“…All tested amino acid substitutions for those two residues (including the conservative Lys substitution for Arg 83) resulted in loss of glucose-6-phosphatase activity. Finally, although most of the conserved amino acids of domain 3 are present in the human glucose-6-phosphatase, those residues were not investigated in that study (Lei et al, 1995). The proposed glucose-6-phosphatase topology model predicts domain 3 on the opposite and noncatalytic side of the membrane from domains I and 2.…”
Section: Dxh-(x25)-gdxxd-(x2s)-gnh(d/e) Sequence Is Foundmentioning
confidence: 91%
“…In addition, earlier experiments on glucose-6-phosphatase indicated that a phosphoenzyme intermediate is formed during catalysis, and that a histidine residue is the phosphoryl acceptor (Feldman & Butler, 1972;Countaway et al, 1988). Using sitedirected mutagenesis to study the structure-function relationship of the human glucose-6-phosphatase, Lei et al (1995) separately introduced amino acid substitutions for Arg 83 and His I19 (the conserved histidine present in domain 2) and tested the mutated enzymes for glucose-6-phosphatase activity. All tested amino acid substitutions for those two residues (including the conservative Lys substitution for Arg 83) resulted in loss of glucose-6-phosphatase activity.…”
Section: Dxh-(x25)-gdxxd-(x2s)-gnh(d/e) Sequence Is Foundmentioning
confidence: 99%
“…The eight-amino acid FLAG marker peptide, DYKDDDDK (Scientific Imaging Systems, Eastman Kodak, CT) was used to tag the amino or carboxyl terminus of G6Pase as described previously (18). The two outside PCR primers for G6Pase mutants that contain mutations upstream of the DraIII site are nucleotides 77-96 (G1; sense) and nucleotides 625-602 of G6Pase-DraIII (I2; antisense) (29), and the two outside PCR primers for mutants that contain mutations downstream of the DraIII site are nucleotides 611-634 (I1; sense) and nucleotides 1150 -1133 of G6Pase-DraIII (G2; antisense). The two outside primers for G6Pase R170Q, G184E, G184V, G188D, and G188R mutants are G1 and G2.…”
Section: Methodsmentioning
confidence: 99%